Relationship Between Handgrip Strength and Isokinetic Shoulder Abduction-Adduction Muscle Strength in Primer Fibromyalgia - Ali Sallı,; Halim Yılmaz,; Hilal Kocabaş,; Hatice Uğurlu, (Archives of Rheumatology, 2008)
Objective: To compare grip strength and isokinetic shoulder abduction- adduction maximal muscle strength and to assess the correlation between hand grip strength (HGS) and shoulder strength in primer fibromyalgia patients with healthy controls. Patients and Methods: One hundred patient and 50 healthy women were included in this study. The patient's complaint duration and number of tender points were recorded. The visual analog scale was used for the assessment of pain. Beck depression scale and Fibromyalgia Impact Questionnaire (FIQ) were calculated. Handgrip strength was measured using a handgrip dynamometer and the highest value of sequential 3 measurements was recorded. Isokinetic shoulder abduction-adduction maximal muscle strength was measured at 60 and 180 degrees/sec. All patients' dominant side was assessed. The strength was calculated as the mean of five consantric isokinetic repetations. Results: There was no statistical difference between patients and the control group in age and body mass index (BMI). The mean HGS was 0,41±0,10 and 0,62±0,13 in the fibromyalgia and the healthy group respectively. The mean HGS and shoulder abduction-adduction maximal muscle strength were significantly lower in the fibromyalgia group than the healthy subjects (p<0,001). Whereas a positive correlation was found between HGS and age, BMI and shoulder abduction- adduction maximal muscle strength, a negative correlation was recorded between complaint duration, VAS and FIQ. Conclusion: Hand grip strength may be a simple and effective method to determine muscle performance of the upper extremity. (Rheumatism 2008; 23: 5-8)